KAJIAN KONSEP DESAIN TAMAN DAN RUMAH TINGGAL HEMAT ENERGI - Prima Kurniawaty; Andi Gunawan; Surjono Surjokusumo (Jurnal Lanskap Indonesia, 2012)
The primary factor of high energy consumption in housing sector is caused by unconformity between architectural and landscape design. Housing design which has been developed and adopted by people now is more oriented towards building aspect and in current trends design, but lack of environmental and landscape aspect. The environment and landscape aspects has a profound influence as the results of this study. Using Analytical Hierarchy Process (AHP) method, the study results in the influence of landscape (site design) on energy saving in housing landscape unit is very significant (67%) compared to building design (33%). In this case, the plant is a ma-jor component that contribute to energy saving design (48.3%). The Criteria for each component are discussed specifically in this paper, both physically and visually.